INTERNATIONAL UNIVERSAL INSTITUTIONAL MECHANISM FOR HUMANITARIAN ASSISTANCE IN CRISES - Syroid, Tetyana (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
Introduction. The issue of providing humanitarian assistance is highly relevant for all categories of individuals suffering from the consequences of armed conflicts, epidemiological and environmental disasters etc. The international universal system of humanitarian assistance aims to alleviate the suffering of affected individuals. A number of institutions with different areas of competence take part in this noble mission. Summary of the main research findings. The article examines the activities of institutions specially established under the auspices of the United Nations in the field of humanitarian assistance. In particular, it defines the role of the UN Office for the Coordination of Humanitarian Affairs, which coordinates its activities with multiple actors involved in the process. The article characterizes the activities of specialized UN agencies, including the Office of the United Nations High Commissioner for Refugees (UNHCR), the World Food Programme (WFP), the World Health Organization (WHO), the Food and Agriculture Organization (FAO), the International Organization for Migration (IOM), the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA), and the United Nations Development Programme (UNDP), each contributing to the overall support of vulnerable population groups. Particular attention is given to the importance of financial support provided to humanitarian operations, highlighting the roles of the Central Emergency Response Fund (CERF) and Country-Based Pooled Funds (CBPFs), among others. Conclusions. Under the auspices of the United Nations, a universal international humanitarian system has been established, consisting of a broad network of actors – including dedicated institutions, financial entities, and specialized UN agencies – which has evolved over the years to effectively respond to humanitarian crises since the adoption of UN General Assembly Resolution 46/182 on strengthening of the coordination of humanitarian emergency assistance. These institutions continually innovate and adapt their practices to deliver more effective, rapid, and responsive assistance tailored to individuals’ specific needs. Despite the sustained efforts of humanitarian organizations, the delivery of aid still fails to meet all the needs of vulnerable population groups. Beyond insufficient funding, humanitarian operations face other major challenges – insecurity, complex logistics, bureaucratic barriers, and the actions of certain authorities who deliberately use or restrict humanitarian aid for their own benefit. The absence of political conditions necessary for effective humanitarian response, including the failure of conflict parties to honour their commitments and to comply with international humanitarian law, further exacerbates these challenges.